2019
DOI: 10.1093/ecco-jcc/jjz123
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Continuous Geboes Score With the Robarts Histopathology Index: Definitions of Histological Remission and Response and their Relation to Faecal Calprotectin Levels

Abstract: Background and Aims The histological status of ulcerative colitis [UC] patients in clinical and endoscopic remission has gained space as an important prognostic marker and a key component of disease monitoring. Our main aims were to compare two histological indexes—the continuous Geboes score [GS] and the Robarts Histopathology index [RHI]—regarding their definitions of histological remission and response, and the ability of faecal calprotectin [FC] levels to discriminate between these status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
2
22
0
2
Order By: Relevance
“…Seven studies 14,[25][26][27][28]30,31 used partially validated scores (Geboes score, Nancy index and Robarts histopathologic score) for histologic remission definition, while in six studies 13,15,29,32,33 histologic healing was based on nonvalidated scores. Comparative trials 31,40,41 revealed a strong correlation between Geboes score, Nancy index and Robarts score suggesting that the available validated scores may provide overlapping data. Instead, a study by Römkens et al 42 showed that the correlation between the nonvalidated scores and between the nonvalidated and validated scores was moderate, highlighting how the histologic score can influence patient management and therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 14,[25][26][27][28]30,31 used partially validated scores (Geboes score, Nancy index and Robarts histopathologic score) for histologic remission definition, while in six studies 13,15,29,32,33 histologic healing was based on nonvalidated scores. Comparative trials 31,40,41 revealed a strong correlation between Geboes score, Nancy index and Robarts score suggesting that the available validated scores may provide overlapping data. Instead, a study by Römkens et al 42 showed that the correlation between the nonvalidated scores and between the nonvalidated and validated scores was moderate, highlighting how the histologic score can influence patient management and therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [36][37][38] confirmed that FC can detect histologic remission and with threshold being lower than that of endoscopic remission. Although a validated cut-off FC to predict histologic remission has not been established, Open access our results confirm the role of FC as a predictive marker for histologic remission in patients with IMDC.…”
Section: Open Accessmentioning
confidence: 98%
“…When assessing the usefulness of FC for predicting the histological degree of inflammation in UC colon, results were quite disappointing as well. 47 The authors conclude that FC levels may be useful to exclude the improvement of histological activity, while caution is required for predicting histological remission, as histological activity may be observed even in cases with normal FC levels. Among the strengths of the ECAP score is its focus on the residual inflammation assessed by histology, whose clinical meaning has not yet been fully defined, even though it has been suggested that a deep remission predicts a better global clinical outcome.…”
Section: Robarts Histopathology Index (Rhi) 2017mentioning
confidence: 93%